1996
DOI: 10.1039/cc9960000923
|View full text |Cite
|
Sign up to set email alerts
|

The first stereospecific synthesis of michellamine B

Abstract: The dimeric alkaloid michellamine B is synthesized stereospecifically by the palladium-catalysed cross-coupling of the 6'-naphthaleneboronic acid of the tetrabenzylated derivative of korupensamine A and the 6'-bromo analogue of the tetrabenzylated derivative of korupensamine B, both of which are prepared by total synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 11 publications
1
28
0
5
Order By: Relevance
“…As another example of the use of the Suzuki coupling to fashion atropisomeric systems, we consider the total synthesis of michellamine B (148, Scheme 28), a representative member of a class of homo-and heterodimeric alkaloid natural products that exhibit potent anti-HIV activity, [134] by Dawson and co-workers. [135] The coupling of enantiomerically pure bromotetrahydroisoquinoline 142 with naphthyl boronic acid 143 under the influence of Ba(OH) 2 and a catalytic amount of [Pd(PPh 3 ) 4 ] in aqueous DME at 85 8C yielded a nearly equimolar mixture of the two atropisomeric products 144 and 145 in a combined yield of 82 %. The teams choice of the Suzuki reaction to effect this coupling was influenced to no small degree by the previously reported model studies of Hoye and Chen, who had demonstrated the clear superiority of this process over both the Stille reaction and the palladiumcatalyzed cross-coupling of zinc derivatives for the union of similarly hindered and electron-rich aryl derivatives.…”
Section: The Suzuki Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…As another example of the use of the Suzuki coupling to fashion atropisomeric systems, we consider the total synthesis of michellamine B (148, Scheme 28), a representative member of a class of homo-and heterodimeric alkaloid natural products that exhibit potent anti-HIV activity, [134] by Dawson and co-workers. [135] The coupling of enantiomerically pure bromotetrahydroisoquinoline 142 with naphthyl boronic acid 143 under the influence of Ba(OH) 2 and a catalytic amount of [Pd(PPh 3 ) 4 ] in aqueous DME at 85 8C yielded a nearly equimolar mixture of the two atropisomeric products 144 and 145 in a combined yield of 82 %. The teams choice of the Suzuki reaction to effect this coupling was influenced to no small degree by the previously reported model studies of Hoye and Chen, who had demonstrated the clear superiority of this process over both the Stille reaction and the palladiumcatalyzed cross-coupling of zinc derivatives for the union of similarly hindered and electron-rich aryl derivatives.…”
Section: The Suzuki Reactionmentioning
confidence: 99%
“…[139] An illustrative example of this , 1996). [135] strategy is found in the synthesis of the alkaloid korupensamine A (152, Scheme 29), [140] a molecule that can be formally considered as the monomeric unit of the michellamine alkaloids alluded to above. Thus, as shown in Scheme 29 a, the Suzuki coupling of naphthyl boronic acid 149 with enantiopure tricarbonylchromium-complexed aryl bromide 150 led to the smooth formation of biaryl system 151 in 88 % yield and as a single stereoisomer.…”
Section: The Suzuki Reactionmentioning
confidence: 99%
“…[131] Bei der Planung dieses Syntheseschritts ist jedoch ein zusätzliches Problem zu beachten, nämlich die Atropisomerie des Kupplungsprodukts infolge der eingeschränkten Rotation um die Biarylachse. [132] So war denkbar, dass die von unserer Arbeitsgruppe ange- [135] einem repräsentati-ven Vertreter einer Klasse homo-und heterodimerer Alkaloid-Naturstoffe mit Anti-HIV-Aktivität. [134] Die Kupplung des enantiomerenreinen Bromtetrahydroisochinolins 142 mit der Naphthylboronsäure 143 in Gegenwart von Ba(OH) 2 Einen interessanten Ansatz zum Problem der Atropisomerie in der Biarylsynthese entwickelten Uemura und Mitarbeiter durch Einsatz von planar-chiralen Tricarbonyl-(aren)chrom-Komplexen [138] in palladiumkatalysierten Kreuzkupplungen.…”
Section: Suzuki-reaktionenunclassified
“…Das bestätigt der zweite Anlauf zur Synthese der revidierten Struktur [142] von Diazonamid A durch unsere Arbeitsgruppe im Jahre 2003. [143] [135] Schema 29. Atropselektive Suzuki-Kupplung eines planar-chiralen Tricarbonyl(aren)chrom-Komplexes in der enantioselektiven Synthese von Korupensamin A (152) (Uemura et al, 2000).…”
Section: Suzuki-reaktionenunclassified
“…They have served as important building blocks in the syntheses of various aromatic natural products, such as ellagitannins (Sanguiin H-5) [1], terpenoids (Frondosin B) [2], alkaloids (Psilocin [3], (-)-Quadrigemine C [4], Singulair [5][6][7], Michellamine B [8,9]), antibiotics (Arylomycin B) [10], and benzofuranes (Lespedezavirgatol) [11].…”
Section: Introductionmentioning
confidence: 99%